Clinical characteristics and clinical outcomes in heart failure patients: a multi-center, multi-ethnic study - Bui Khiong, Chung; Hwei Sung, Ling; W. K., Ho; A.Z. Y., Koh; C. Z. F., Chua; J. K. W., Wong; R.S.L., Chew; K. C., Cheah; C. H., ChaI; L. Y., Ting; S. L., Kwa; J., Namasoo; et al. (European Society of Cardiology, 2025)
Background: Heart failure (HF) remains a significant cause of morbidity and mortality globally, with an increasing prevalence driven by an aging population and improved survival rates of patients with cardiovascular conditions. Evidence indicates that regional and ethnic variations may influence the clinical characteristics and outcomes of HF patients in different middle-income countries. Objectives: We aim to evaluate the clinical characteristics, guideline-directed medical therapy (GDMT) prescription patterns, and outcomes of HF patients in our region. Methods: This is a retrospective cohort study encompassing HF clinic patients followed up in 10 hospitals from 1st January 2021 to 30th June 2023. Data were collected on demographic profiles, comorbidities, GDMT prescription, New York Heart Association (NYHA) class, left ventricular ejection fraction (LVEF), and clinical outcomes, including mortality and hospital readmissions. Results: A total of 578 patients (mean age 56±14 years, 76.1% male) were included. Most patients presented with HFrEF (88.5%) and NYHA class II (51.8%). 45.6% of patients were from local ethnic groups. Comorbidities were prevalent, including hypertension (67.8%), dyslipidaemia (52.9%), diabetesmellitus (40%), ischemic heart disease (44.1%), chronic kidney disease (27.5%), anaemia (27.4%) and atrial fibrillation (23.1%). During the first visit, the mean heart rate, systolic and diastolic blood pressure was 79, 126 and 76 respectively. Utilization of natriuretic peptide as biomarker was low (12.5%) with mean of NT-proBNP 2005.5 pg/ml. The mean eGFR according to EPI-CKD was 74.4 mL/min. The mean for serum urea, serum potassium and haemoglobin level was 6.7 mmol/L, 4.2 mmol/L and 13.5 g/dL, respectively. The mean QRS interval was 110ms. 21% of patients had a QRS interval of > 120ms. At the 6-month follow-up, GDMT for HF patients was optimized as follows: renin-angiotensin-aldosterone system inhibitors (88%), beta-blockers (94%), mineralocorticoid receptor antagonists (86.4%), and sodium-glucose cotransporter-2 inhibitors (55.5%). Device therapy utilization remained low at 3.6%. HF patients showed improvements in NYHA class (NYHA I: 31.5% to 65.1%; p<0.001) and LVEF (27.5±9.0% to 39.0±13.5%; p<0.001) over 6 months. The 6-month composite outcome of all-cause mortality, HF readmissions and urgent visits was 18.8%, with all-cause mortality at 8.9%, HF readmissions and urgent visits at 12.4%. Conclusion: Heart failure patient in our region were younger and high prevalence of cardiovascular risk factors.